Cytomorphologic Evidenceof Human Papillomavirus Infection in Smears from the IrradiatedUterine Cervix - Longatto Filho, Adhemar [UNESP]; Sakamoto Maeda, Marina Yoshie [UNESP]; Oyafuso, Marina Suheko [UNESP]; Alves, Venancio Avancini Ferreira [UNESP]; Kanamura, Cristina Takami [UNESP]; Bortolan, Jeni [UNESP] (Karger Publishers, 1997)
OBJECTIVE: To report the cytomorphologic evidence of human papillomavirus (HPV) infection in cervical smears from women treated with radiotherapy for carcinoma of the uterine cervix. STUDY DESIGN: From January 1986 to December 1993, 32 cervical cytologic smears (CCSs) from women who had received radiotherapy (Rtx) for squamous cell cervical carcinoma at A. C. CamargoCancer Hospital were selected for study due to the presence of signs of HPV infection. Review of the files of these patients showed 22 additional samples, which we included in this study. The avidinbiotin- immunoperoxidase technique was performed on previously stained slides using polyclonal rabbit antibovine papillomavirus type 1 to confirm the HPV infection. RESULTS: Positive reactions were found in 18 cases (27 samples), mainly in cells with classic koilocytotic features, but also in epithelial cells that lacked cytopathic effects. Only one case, a biopsy from a verrucous lesion observed after Rtx, was found to be positive for HPV 6/11 DNA by in situ hybridization. CONCLUSION: Cytologic and immunohistochemical positivity for HPV, as well as the reaction with a HPV 6/11 DNA probe, strongly suggested that HPV infection was acquired or expressed after radiotherapy. Further studies are needed to assess the mechanisms responsible forsuch an association. © 1997 The International Academy of Cytology Acta Cytologica.
Keywords: Cervix neoplasms; Human; Papillomavirus; Radiotherapy